Dietary pattern of the elderly people: a comparison between urban and rural communities - Dillruba, Nurun Nahar; Barua, Sagarmay (Bangladesh Journal of Nutrition, 2018)
This is a cross sectional study conducted amongst 200 randomly selected urban and rural elderly people of age 60 to 90 years. The group of urban sample was selected randomly in Dhaka city. The rural group was randomly selected from villages of Sonargaon thana under Narayanganj district. The location was selected purposively. The purpose of this study was to investigate the dietary pattern of the elderly people. Dietary data was collected by a 24-hour recall method along with a seven days food consumption frequency. AU urban and rural participants were found to consume rice, cooking oil and iodized salt every day. More than half (51%) of the urban elderly people were found to take pulse or legumes 3-6 days per week. On the other hand, half (50%) of the rural elderly people were found to take pulse or legumes only 1-2 days per week. Majority of the urban (74%) and rural (73%) elderly people were found to take small fish 1-2 days per week. A good percentage of urban (68%) and rural (62%) elderly people were found to take big fish1-2 days per week. About 33% of urban and 31% of rural elderly people were found never to take milk in a week. Twenty nine percent urban and 19% rural elderly people were found to take milk everyday in a week. A higher proportion of the urban (71%) and rural (69%) elderly people were found to take Green leafy vegetables (GLV) only1-2 days per week. A higher proportion of the urban (66%) and 56% rural elderly people were found to take citrus fruits only 1-2 days per week. Rice (p<0.01) and potato (p<0.05) intake was found to be significantly higher for rural elderly people as compared to their urban counterpart. In contrast wheat, milk and milk product, oil, pulse and nuts (p<0.01), sugar and meat intake (p<0.05) was found to be significantly higher for urban elderly people as compared to their rural counterpart. Energy, protein, fat, iron, thiamine, riboflavin and zinc intake was found to be significantly (p<0.01) higher for urban elderly people as compared to the rural one. Carotene intake was found to be in a higher trend for rural elderly people as compared to their urban counterpart. Energy intake was found to be lower than the RDA for both urban and rural elderly people. Protein intake was found to be higher than the RDA for urban elderly and lower than the RDA for rural elderly people. However, the urban elderly people are better off in terms of their energy and nutrients intake as compared to their rural counterpart. Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 39-45